Prevalence of Factor V Leiden in Patients with Myocardial Infarction and Normal Coronary Angiography - Mansourati, Jacques; Da Costa, Antoine; Munier, Stéphane; Mercier, Bernard; Tardy, Brigitte; Ferec, Claude; Isaaz, Karl; Blanc, Jean-Jacques (Thrombosis and Haemostasis, 2000)
Factor V Leiden is associated with an increased risk of venous thrombosis and myocardial infarction in young women, but not in men in this latter case. The aim of this study was to evaluate the prevalence of this mutation in patients with myocardial infarction but normal coronary angiography.We compared 3 groups of patients: one group consisted of 107 patients with premature myocardial infarction but no significant coronary artery stenosis; another group of 244 patients with myocardial infarction and significant coronary artery stenosis; a third group of 400 healthy controls.Factor V Leiden was found in 13 patients (12.1%) who had a myocardial infarction without significant coronary artery stenosis, 11 patients (4.5%) who had a myocardial infarction with significant coronary artery stenosis (p = 0.01) and in 20 controls (5%) (p = 0.01). Odds ratio associated with factor V Leiden were respectively 2.93 (CI95 : 1.18-7.31) and 2.63 (CI95 : 1.19-5.78) when we compared myocardial infarction patients without significant coronary artery stenosis to controls or to patients with significant coronary artery stenosis.In myocardial infarction patients without significant coronary artery stenosis, prevalence of factor V Leiden is significantly higher than in controls. This new finding supports the hypothesis that thrombosis plays a key role in this selected situation.
Keywords: Coagulation; myocardial infarction; thrombosis; genetics